The impact of persistent herpesvirus infection on immunity and vaccination response - Volyanskiy, A; Кuchma M; Kolotova, T; Кlyisa T; Кuchma I; Konoreva Е; Smelyanskaya М; Peremot, S; Каshpur N; Davydenko М (Annals of Mechnikov’s Institute, 2020)
In this review we summarize current knowledge on the ability of latent herpesviruses to modulate the immunity and response to vaccination. Nearly all humans are latently infected with multiple herpesviruses but little is known about virus-host interactions. Meanwhile, the study of the immune response to Epshtein-Barr virus (EBV) and сytomegalovirus (CMV) has revealed significant regulatory effects on the immune system. During the primary infection a human cytomegalovirus is predominately found in peripheral blood monocytes and polymorphonuclear leukocytes. However, the virus can not be replicated in these cells. CMV induces the survival and differentiation of infected monocytes into long-lived macrophages capable of supporting viral replication and the release of virions, which infect CD34+ myeloid progenitor cells. CMV latently persists in myeloid progenitor cells and monocytes and reactivates during their differentiation into macrophages. CMV-infected monocytes exhibit a unique reprogramming of their differentiation and secret both pro-inflammatory M1- and anti-inflammatory M2-associated cytokines. But cytomegalovirus induced macrophage phenotype skewed towards pro-inflammatory M1 type. MV has profound effects on the composition and function of both T cells and NK cells. CMV constantly reactivates during differentiation of monocytes into macrophages. Consequently, persons with latent CMV infection have substantially increased numbers and proportions of CD8+ T cells that lead to exhaustion and an early onset of immunosenescence. Also, it has been shown that the latent CMV virus infection markedly increases the proportion of NK cells expressing the activating NKG2C receptor. So, it has been proposed that CMV alters the composition of T cell and NK cell subsets and accelerates immune aging. Given the capacity of CMV to alter a macrophage, as well as NK and T cell responses it is reasonable to hypothesize that latent infection would alter the outcome of vaccination. The EBV virus remains in memory B cells throughout life. In healthy subjects the EBV remains latent in the latency phase 0 and EBV replication proceeds without production of infectious virions. But the virus can be reactivated in latency phases 1, 2 and 3. The virus reactivation can affect immunity and results in diseases. Chronic fatigue syndrome (CFS) is characterized by fatigue, exhaustion and flu-like symptoms. EBV latent reactivation in CFS patients is supported by certain data. In a subset of patients, CFS begins with infectious mononucleosis and enhanced EBV-specific antibody titers have been reported. Also, a profound deficiency in EBV-specific B and T cell memory response was observed in a majority of CFS patients. These data confirmed the EBV virus involvement in the CFS development. Cytokine dysregulation, decreased natural killer cell functioning, the presence of autoantibodies, and a reduced response of T cells to mitogens have been reported in CFS. But if immunity is disturbed in CFS patients, they might have an altered response to vaccination. Herpes viral reactivation has been documented in sepsis. Demonstration of the widespread reactivation of latent herpesviruses in sepsis provides strong evidence that sepsis results in functional immunosuppression. Reactivation of latent viruses may be associated not only with sepsis but with aging as well. Moreover, according to our data herpesvirus reactivation is common in recurrently infected children. These observations highlight the ability of herpesviruses to profoundly impact the host immune function. But the recent publications have shown that persistent herpesvirus infection can be beneficial for the host. The data obtained from the multiple mouse models demonstrate the potential for herpesvirus infection to enhance resistance against a secondary infection. It has been documented that during latent murine cytomegalovirus or murine gammaherpesvirus infection 68 mice are protected against lethal bacterial infections by prolonged macrophage activation and IFNγ secretion. Little is known about the potential benefits of herpesvirus latency in humans. The effect of CMV on vaccine responses is controversial. It is well known that vaccine responses is reduced in aging populations. CMV accelerates immune aging and may further reduce the response to vaccination. In fact, some studies show a negative effect of CMV while others showed no difference in CMV+ vs CMV− in older individuals. Conversely, in young individuals, a negative association between the CMV antibody titer and the response to the influenza vaccine has been found. Also, a negative association between the CMV antibody titer and the response to the influenza vaccine was found in young individuals. But, according to another results CMV enhances the immune responses of younger individuals to influenza vaccination. In summary, the hypothesis that CMV virus accelerates immunosenescence and decreases vaccination response is controversial. Moreover, CMV infection may enhance the immune responses in children and young individuals. Vaccinations can induce the aberrant immune response of CFS. But the available data do not support the CFS impact on the vaccination response. In conclusion, the host-persistent herpesviruses infection history is likely to play a significant role in the immune system response to vaccination.